Pathogenetic aspects of the development of psoriatic arthritis in people with generalized chronic periodontitis - G. V. Poryadin; A. N. Zakhvatov; A. Yu. Parshina (Бюллетень сибирской медицины, 2023)
The pathogenetic mechanisms of progression of chronic periodontitis and psoriatic arthritis have common components in immune and inflammatory responses.The pathogenesis of chronic periodontitis involves interaction of microbial and immunological components. As a chronic immune-mediated inflammatory disease and a consequence of an infectious trigger that originally affects gingival soft tissue, periodontitis is typically characterized by periodontal destruction and damage to adjacent connective tissues. Neutrophils contribute to the development of periodontitis and participate in its progression by recruiting T helper 17 cells and stimulating synthesis of the receptor activator of the nuclear factor kappa-β ligand (RANKL), contributing to bone resorption.Macrophages as producers of proinflammatory cytokines (interleukin (IL)-1β, IL-6, IL-22, IL-23, tumor necrosis factor (TNF)), free radicals, and matrix metalloproteinases contribute to the chronic course of the disease. Tissue destruction results in generation of reactive oxygen species by neutrophils, which, against the background of a decrease in the antioxidant potential, leads to development of oxidative stress. These processes together lead to tooth mobility, formation of periodontal pockets, and bone resorption.The key factors in the formation of psoriatic arthritis against the background of periodontitis are overproduction of proinflammatory cytokines in target tissues (skin, joints, gingival microflora) and development of an excessive systemic immune response to the microbiota inhabiting the epithelial and periodontal tissues. A statistically confirmed correlation of the progression of periodontal destruction with the presence of psoriatic arthritis proves the significance of the effects of inflammation as a background for the progression of a comorbidity. Increased IL-17 synthesis plays a crucial role in the development of immune responses of pathological bone remodeling and bone resorption in periodontitis and psoriatic arthritis.